Electron and photon efficiencies in LHC Run 2 with the ATLAS experiment - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Journal of high energy physics, 2024)
Precision measurements of electron reconstruction, identification, and isolation efficiencies and photon identification efficiencies are presented. They use the full Run 2 data sample collected by the ATLAS experiment in pp collisions at a centre-of-mass energy of 13 TeV during the years 2015-2018, corresponding to an integrated luminosity of 139 fb−1. The measured electron identification efficiencies have uncertainties that are around 30%-50% smaller than the previous Run 2 results due to an improved methodology and the inclusion of more data. A better pile-up subtraction method leads to electron isolation efficiencies that are more independent of the amount of pile-up activity. Updated photon identification efficiencies are also presented, using the full Run 2 data. When compared to the previous measurement, a 30%-40% smaller uncertainty is observed on the photon identification efficiencies, thanks to the increased amount of available data.